Optimal synthesis versus dynamic analysis for an acrobatic aerial movement - Leboeuf, F.; Seguin,P.; Lacouture, P. (Science et motricité, 2012)
A predictive method: the optimal synthesis, based on an optimal dynamic problem, was solved for generating the aerial phase of a backward somersault. Optimal joint torques were compared with those resulting from inverse dynamics. A gymnast was modeled as a planar seven-segment multibody system with six internal degrees of freedom. The aerial motion was generated using a parametric optimization technique. The performance criterion minimized the time integral of quadratic joint torques. Optimal synthesis has produced a somersault closely mimicking the experimental one. Optimal joint torques revealed the motor control at the knee after takeoff unattainable by inverse dynamics analysis because of the measurement uncertainty propagation. Moreover, our study suggests that minimization of joint torques might be the primary control objective of a backward somersault.